Testing Weak Form of Market Efficiency in Nepal - Dangol, Jeetendra (The International Research Journal of Management Science, 2016)
The paper investigates the weak form of market efficiency for overall and sectorial indices. The Nepalese stock returns are found not being normally distributed during the study period. The autocorrelation of the stock returns was reduced by correcting the data with the application of the methodology suggested by Miller et al. (1994). The Nepalese stock market has suffered from the problem of thin-trading. Overall, the Nepalese market is not weak-form efficient on the basis of the analysis performed by employing observed returns series; but it is found a weak-form efficient in case of the analysis while using corrected data after adjusting infrequent trading. Hence, the study is supported to the random-walk and weak form of market efficiency.